The efect of exercise on balance in patients with stroke, Parkinson, and multiple sclerosis: a systematic review and meta-analysis of clinical trials - Salari, Nader; Hayati, Aida; Kazeminia, Mohsen; Rahmani, Adibeh; Mohammadi, Masoud; Fatahian, Reza; Shohaimi, Shamarina (Springer Milano, 2021)
Background: Stroke, Parkinson, and multiple sclerosis are a range of diseases affecting the nervous system and show balance impairments due to damage of the balance control system. Many early articles have been published on the effect of exercise on balance in patients suffering from neuromuscular diseases. However, a comprehensive study showing a clear result of these three diseases was not found. Hence, the purpose of the present meta-analysis and systematic review is to determine the effect of exercise on balance in people with stroke, Parkinson, and multiple sclerosis. Methods: According to the PRISMA 2009 multi-step instructions, keywords related to the purpose of the research were browsed in the MeSH browser databases; IranDoc, MagIran, IranMedex, SID, ScienceDirect, Web of Science (WoS), ProQuest, Medline (PubMed), Scopus, and Google Scholar were searched to extract articles published in Persian and English language. The search process for retrieving the articles in the sources mentioned from January 01, 2000, to December 30, 2020, was done. The heterogeneity index of the studies was determined using the I2 test. Given the heterogeneity, the random-effects model was used to combine the articles and the results. Results: Initially, 7067 articles were found, but after removing duplicate and irrelevant articles, 96 clinical trials with a sample size of the intervention group of 1760 people were included in the study. As a result of the articles’ composition, the mean balance score index after exercise in the intervention group showed a significant increase of 0.67 ± 0.12 of the unit (P˂0.01). The highest rate of increase in the balance score after the intervention was reported in patients with myelomeningocele with 1.66 ± 0.3 unit (P˂0.01). Conclusion: Considering the positive effect of using exercise on increasing the balance in patients with stroke, Parkinson, and multiple sclerosis, it is recommended that health care providers implement a regular exercise program to improve the condition of these patients.